Identification of two functional xyloglucan galactosyltransferase homologs BrMUR3 and BoMUR3 in brassicaceous vegetables - Wang, Meng; Xu, Zongchang; Guo, Shuaiqiang; Zhou, Gongke; ONeill, Malcolm; Kong, Yingzhen (PeerJ, 2020)
Xyloglucan (XyG) is the predominant hemicellulose in the primary cell walls of most dicotyledonous plants. Current models of these walls predict that XyG interacts with cellulose microfibrils to provide the wall with the rigidity and strength necessary to maintain cell integrity. Remodeling of this network is required to allow cell elongation and plant growth. In this study, homologs of Arabidopsis thaliana MURUS3 (MUR3), which encodes a XyG-specific galactosyltransferase, were obtained from Brassica rapa (BrMUR3) to Brassica oleracea (BoMUR3). Genetic complementation showed that BrMUR3 and BoMUR3 rescue the phenotypic defects of the mur3-3 mutant. Xyloglucan subunit composition analysis provided evidence that BrMUR3 and BoMUR3 encode a galactosyltransferase, which transfers a galactose residue onto XyG chains. The detection of XXFG and XLFG XyG subunits (restoration of fucosylated side chains) in mur3-3 mutants overexpressing BrMUR3 or BoMUR3 show that MUR3 from Brassica to Arabidopsis are comparable as they add Gal to the third xylosyl residue of the XXXG subunit. Our results provide additional information for functional dissection and evolutionary analysis of MUR3 genes derived from brassicaceous species.
Keywords: Xyloglucan; MUR3; Cell wall; Brassicaceous; Brassica rapa; Brassica oleracea